Influence of the maturity of Musa paradisica peels on mild steel corrosion in sulfuric acid - Ji G.; Singh S.K.; Prakash R. (My University, 2025)
Natural materials (NMs) are the preferred choice of scientists for metal protection due to their economic viability, zero harmful effects and easy protocols for use. NMs are electrochemically adhered to the metals surface and protect them in violent media. In this work, adsorption properties of Musa Paradisica peels on mild steel (MS) in sulfuric acid solutions are studied. To investigate the effect of maturity of peels on adsorption properties, three extracts have been prepared based on maturity of the peels. The examination of all the extracts have been carried out by UV-visible spectroscopy (UVVS), FTIR spectroscopy (FTIS), weight loss measurements (WLM), open circuit potential (OCP) curves, electrochemical impedance spectroscopy (EIS), Tafel polarization curves (TPC), and linear polarization resistance (LPR). The findings of the work announce that the extracts are rich in biological molecules and provide good protection (TPC: maximum 87%, minimum 72%) to MS against sulfuric acid attack. The adsorption effects on MS surface are also monitored through scanning electron microscopy (SEM) and atomic force microscopy (AFM), which claims that the extracts are adhered on MS and doing inhibition in the acid. Langmuir isotherms are employed to do the comparative investigation of the extracts adsorption on MS, which indicate that the difference in the effectiveness of the extracts are related with their adsorption on MS. Adsorption and adsorption characteristics of the extracts are also studied by Density functional theory (DFT) calculations, which confirm the conclusions of Langmuir isotherms. © 2021 Informa UK Limited, trading as Taylor & Francis Group.